Measurements of the $Υ$(1S), $Υ$(2S), and $Υ$(3S) differential cross sections in pp collisions at $\sqrt{s} =$ 7 TeV - CMS collaboration (2140 authors) (2015)
Differential cross sections as a function of transverse momentum pT are presented for the production of ϒ(nS) ( n = 1, 2, 3) states decaying into a pair of muons. Data corresponding to an integrated luminosity of 4.9 fb−1 in pp collisions at s=7TeV were collected with the CMS detector at the LHC. The analysis selects events with dimuon rapidity |y|<1.2 and dimuon transverse momentum in the range 10<pT<100GeV . The measurements show a transition from an exponential to a power-law behavior at pT≈20GeV for the three ϒ states. Above that transition, the ϒ(3S) spectrum is significantly harder than that of the ϒ(1S) . The ratios of the ϒ(3S) and ϒ(2S) differential cross sections to the ϒ(1S) cross section show a rise as pT increases at low pT , then become flatter at higher pT .